Does time matter? Impact of financial decision-making abilities on financial choices mediated by time perspective - Arif, Imtiaz; Khan, Lubna; Irshad, Nida (Serbian Journal of Management, 2024)
The aim of this paper is to examine the relationship between financial decision-making ability and financial choices, and also to check the mediating role of time perspective in this relationship. Financial decision-making ability is composed of two factors: financial behavior (FB) and financial literacy (FL). Whereas, three financial choices are used, which are: investment, savings, and consumption. Using structural equation modeling (SEM), the sample of 380 participants was used to analyze the results. The findings indicate that both financial literacy and financial behavior significantly increase the investment and choices of individuals, while financial behavior also increase consumption. In addition, study found that different factors of time perspective also mediate the relationship between financial decision-making ability and financial choices. The paper concludes with significant policy implications.